Studi Konseptual Upaya Pelestarian Tinggalan Budaya Kawasan Batujaya Melalui Pendekatan STEAM dalam Pendidikan - Mita Indraswari; Hafnidar; Isman Pratama Nasution (AMERTA, 2026)
Abstract. A Conceptual Study on Preservation of Batujaya Sites Through a STEAM Approach in Education. Preservation of cultural heritage is a dynamic process mandated by Law No. 11 of 2010 concerning Cultural Heritage and UNESCO guidelines, both of which emphasize the critical role of community participation. The Batujaya Site represents evidence of early civilization on the northern coast of Java Island, requiring sustainable preservation efforts by instilling its significance in the younger generation. This study aims to formulate the integration model of cultural heritage preservation at the Batujaya Site into school curricula to enhance students' understanding and pride, empowering them as active agents of heritage conservation. The research provides functional solutions for preservation and education by fostering public education through the STEAM (Science, Technology, Engineering, Arts, and Mathematics) framework. STEAM is a transformative educational approach by utilizing the results of cultural heritage research with school learning. Utilizing a literature study method, this research synthesizes various studies concerning the Batujaya Site and STEAM approach. The implementation of multidisciplinary STEAM learning has been proven to provide critical and concrete learning experiences in several European and Asian countries, including Indonesia. The findings of this study are expected to not only enhance students' critical and innovative thinking skills but also contribute to the long-term sustainability of cultural heritage preservation. Research on the integration of cultural heritage preservation and STEAM represents a novel contribution to heritage preservation studies in Indonesia. The proposed integration model is expected not only to enhance students’ critical and innovative thinking skills but also to contribute to sustainable cultural heritage preservation. Keywords: Batujaya Site, Sustainable Preservation, STEAM, Public Education, Cultural Heritage   Abstrak. Pelestarian cagar budaya merupakan upaya dinamis yang diamanatkan oleh Undang- Undang No. 11 Tahun 2010 tentang Cagar Budaya dan UNESCO dengan menekankan pentingnya partisipasi masyarakat. Kawasan Batujaya adalah bukti peradaban awal di pesisir Utara Pulau Jawa, memerlukan upaya pelestarian berkelanjutan melalui pengenalan nilai penting kepada generasi muda. Penelitian ini bertujuan untuk merumuskan model integrasi pelestarian tinggalan budaya di Kawasan Batujaya ke dalam pembelajaran di sekolah untuk meningkatkan pemahaman dan rasa bangga pelajar sebagai agen aktif pelestari cagar budaya. Manfaat penelitian ini untuk memberikan solusi berdaya guna bagi pelestarian dan pendidikan dalam mendorong keterlibatan publik melalui pendekatan pendidikan publik yaitu STEAM (Science, Technology, Engineering, Arts, and Mathematics). STEAM menjadi pendekatan edukatif yang transformatif dengan memanfaatkan hasil penelitian tinggalan budaya dengan pembelajaran di sekolah. Metode yang digunakan dalam penelitian ini adalah studi literatur dengan mengumpulkan berbagai hasil kajian mengenai Kawasan Batujaya dan STEAM. Penggunaan STEAM pada pembelajaran di sekolah dengan implementasi multidisiplin ilmu telah terbukti memberikan pengalaman belajar kritis dan konkret bagi pelajar di beberapa negara Eropa dan Asia termasuk di Indonesia. Penelitian mengenai integrasi tinggalan budaya dengan STEAM menjadi kajian baru dalam kajian pelestarian tinggalan budaya di Indonesia. Model integrasi ini menjadi hasil penelitian yang diharapkan tidak hanya meningkatkan keterampilan berpikir kritis dan inovatif pelajar namun juga dapat meningkatkan pelestarian cagar budaya yang berkelanjutan. Kata kunci: Kawasan Batujaya, Pelestarian Berkelanjutan, STEAM, Pendidikan Publik, Cagar Budaya